Tai Chen's Inquiry into Goodness - Cheng, Chung-Ying (University of Hawai'i Press, 2023)
From Sung times, and throughout the Ming period, one of the dominant philosophies of China had been a dualistic rationalism thought to be firmly grounded on the classics. Tai Chen (1723-1777) was a scholar and philosopher during the Ch'ing period- a time when China produced few philosophic thinkers. He was the greatest of these, and his views are embodied chiefly in Yuan Shan and in Meng Tzu txu-yi shu-cheng. In place of the prevailing Sung dualism, Tai Chen propounded a rationalistic monism seldom before insinuated in a Chinese philosophy. He declines to accept current dogmas and preferred to seek his own truths. His commentaries opposed the time-honored interpretations of Chu Hsi, and he discredited them on purely philosophical grounds. But with few disciples to carry on his teachings, he was virtually forgotten or ignored in China for more than a hundred years after his death. It was not until early in the present century- with China under the pressures of Western aggression and internal disorders-that Tai Chen's nearness to Western thought was rediscovered and his important role in the history of philosophy recognized. Curiously, this first of China's Western-oriented philosophers even today remains little known in the West and his major writings largely untranslated.